Development of a flip-chip composite interconnection system - Wong, Stephen Chee Khuen (2012)
The objective of this research is to develop a novel flip-chip composite interconnect structure to overcome the inherent weaknesses of the conventional solder bump interconnection. In the conventional flip-chip, 3-D stacking of chips is often not feasible due to the inherent solder bump collapse during reflow. The under-bump-metallization (UBM) compatibility with Pb-free solder is a concern, especially with the miniaturization trend. The thin UBM is susceptible to electromigration and metal diffusion. The proposed flip-chip composite structure comprises a Cu pillar with a pinhead on its end which serves as an extended pad for solder bump attachment. The concern of UBM failure on a chip is mitigated as the pinhead which replaces the pad metallization on the chip is extended on a Cu pillar. The chip is no longer exposed to solder reaction during the reflow process. An electrolytic Ni-Au UBM scheme is selected for the Cu pinhead (CPH) pillar bump as the UBM deposition can be carried out in the same plating process for CPH pillars fabrication. Sn-Ag-Cu (SAC) solder and Ni-Au UBM interfacial reaction was investigated. EDX analyses identified a (Ni,Cu)3Sn4 IMC on the Ni UBM interface and a second layer of (Cu,Ni)6Sn5 was formed on top of the (Ni,Cu)3Sn4 IMC. The Ni UBM dissolution after reflow and isothermal aging is approximately 1 µm. A UBM thickness of 2.0 -2.5 µm is recommended for the CPH pillar bump solder attachment.